Pediatric hydatidosis in the south-east of the Buenos Aires province, Argentina - Dopchiz, M. C. (2009)
Fil: Dopchiz, M. C. Universidad Nacional de Mar del Plata. Laboratorio de Zoonosis Parasitarias; Argentina.